2011
DOI: 10.5539/ijef.v3n4p138
|View full text |Cite
|
Sign up to set email alerts
|

Financial Volatility Forecasting by Nonlinear Support Vector Machine Heterogeneous Autoregressive Model: Evidence from Nikkei 225 Stock Index

Abstract: Support vector machines (SVMs) are new semi-parametric tool for regression estimation. This paper introduced a new class of hybrid models, the nonlinear support vector machines heterogeneous autoregressive (SVM-HAR) models and aimed to compare the forecasting performance with the classical heterogeneous autoregressive (HAR) models to forecast financial volatilities. It was observed through empirical experiment that the newly proposed hybrid (SVM-HAR) models produced higher predicting ability than the classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The HAR-RV model was developed in accordance with the heterogeneous market hypothesis proposed by Muller et al (1997) and the long memory character of realised volatility by Andersen et al (2003). Empirical studies have shown that the HAR model has high forecasting performance for future volatility, especially for out-of-sample data with different time horizons (Corsi 2003;Khan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The HAR-RV model was developed in accordance with the heterogeneous market hypothesis proposed by Muller et al (1997) and the long memory character of realised volatility by Andersen et al (2003). Empirical studies have shown that the HAR model has high forecasting performance for future volatility, especially for out-of-sample data with different time horizons (Corsi 2003;Khan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the large amount of papers that refer to the application of ANNs for financial time series forecasting (e.g. White (1988), Khan (2011)), only few works focus specifically on their application on forecasting conditional volatility. The majority of these studies foresees the combination of a GARCH model with a NN architecture, see for example Donaldson and Kamstra (1997) and Hu and Tsoukalas (1999), with few exceptions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This nonlinear and complex nature of stock market makes SPP more difficult [7,8]. The prediction of future stock prices is defined by factors like data intensity, noise, non-stationary, random nature, uncertainties and invisible interlinks [9][10][11]. Generally, there are two classifications of SPP which includes the SPP movement and predicting the value of the stock price.…”
Section: Introductionmentioning
confidence: 99%